Prespektif Hukum Islam terhadap Praktik Jual Beli Menggunakan Potongan Harga (Diskon) dengan Berjangka Waktu di Pusat Perbelanjaan Ramayana Kota Salatiga - Afibatus Afida; M. Taufiq Zamzami (Universitas Muhammadiyah Makassar, 2020)
Abstract : Discount is one of the strategies in buying and selling to given the buyers at fixed price. Usually the seller cut a portion of the price from the original price, so the discount is smaller than the original price and use the percentage. Many assumptions from the public that rise the discount is higher prices, so that if given a discount it looks cheap like buy things at half price. This is interesting from an Islamic point of view to find out the cause of the discount in Ramayana Salatiga. The purpose of the research is knowing the perspective of Islamic law on the practice of buying and selling use the discount with timed. The results is based on the Qur’an, Hadis, and issued by the MUI allow the giving of discount, but must avoid usury, fraud, and harm one of the parties.